Pengaruh Pembelajaran Menyenangkan terhadap Hasil Belajar Peserta Didik pada Kelas VII SMP Negeri 3 Pontianak - Sulindra, Dedi; Munaldus, Munaldus; Rustam, Rustam (Lembaga Yasin AlSys, 2024)
Mathematics learning aims to make it easier to solve various problems in everyday life, ranging from simple problems to very complex problems. Therefore, all participants are encouraged to enjoy, master and understand mathematics well. To master and understand mathematics well, every student needs a high interest in learning mathematics. There are many ways to arouse students' interest in learning, one of which is by creating a pleasant learning atmosphere. So, the way to arouse students' interest in learning lies in the teacher's ability to design and implement fun learning strategies. The aim of this research is to examine the influence of fun learning on student learning outcomes in class VII SMP Negeri 3 Pontianak. Examining how much influence fun learning has when applied to classroom learning. This study employs a quantitative research method. The findings indicate a substantial impact on student learning outcomes. Obtained from the results of research data which shows sig (2-tailed) is 0.000, which means 0.000 < 0.05.